Digital Subtraction Radiography - A Technique Revisited - Anshul Mehra; Amar A Sholapurkar; Auswaf Ahsan; Keerthilatha M Pai (Wolters Kluwer Medknow Publications, 2007)
Digital imaging has changed the scenario of medical and dental imaging as it has been able to address many limitations associated with traditional film based radiograph. However, subtle changes on the image are still difficult to appreciate by the human eye because the changes are buried in a background of normal anatomic structures, and are not clearly evident. Digital subtraction radiography is one of the image enhancing technique which addresses this problem and has found its use in various fields of dentistry in the recent past. However, there is lack of review in the literature regarding this widely used technique. The purpose of this article is to present an overview of this technique and its uses in various fields of dentistry.